(untitled) (Jurnal Teknologi (Sciences & Engineering), 2024)
Pavement industry requires substantial modifications in terms of materials. Stakeholders are in need to opt the solutions of semi-rigid design mix with recycled materials. Necessary evaluations in terms of experimental measures are initially required to represent characteristics properties. Moreover, the behavior to be assessed is rut depth measurements through the implications of wheel tracker apparatus and in accordance with prescribed standards. The mix with specified curing days is being differentiated through subsequent directions focusing choice of recycled materials. The paper presents a model to excel distinguished properties inclusive of the analysis for maintaining air voids, induction of grouting material and stability. The output-oriented data is justified within the enumerations of rut depths for grouted samples. It is analyzed for 25%, 30% and 35% air voids in conditioned to fresh and recycled aggregates. The deliberations are meant with 91 and 13 sample combinations of aggregates and hot mix asphalt respectively followed by the significant tests on bitumen and grouting material. It is observed that critical samples are passed in the configurations of rut depths when processed with reclaimed and construction waste materials at 35% voids. The research data entails its affectivity due to the uniqueness in superior model of current scenario.